Smart-Agro: Enhancing Crop Management with Agribot - T., Krishna Prasath V.; G., Sushanth Reddy; K., Krishna kaanth; K., Madanmohan Reddy (Journal of ISMAC, 2024)
The Agri-Bot robotic system indeed characterizes a substantial advancement in modern agriculture, offering a multifaceted solution for monitoring and managing agricultural environments. By integrating various Arduino-based sensors and motor drivers, it provides a comprehensive toolkit for farmers to effectively oversee their crops' health and optimize resource usage. The inclusion of pH and moisture sensors enables real-time monitoring of soil conditions, allowing farmers to adjust irrigation and fertilizer application precisely according to the plants' needs. Additionally, the DHT11 sensor offers insights into ambient conditions crucial for plant growth, such as temperature and humidity, facilitating informed decision-making. The incorporation of the L298 motor driver further enhances the system's capabilities by enabling automation of tasks like irrigation and seed sowing with precision and efficiency. This integration of robotics and sensor technology not only streamlines agricultural processes but also empowers farmers with data-driven insights to optimize crop growth and sustainability.
Keywords: Agri-Bot; Crop Management; IoT (Internet of Things); Robotics; Data Analytics